Gender Representation in Indonesian EFL Textbooks: A Sociolinguistic Study of “English for Nusantara” - Yolanda, Chindy; Syafryadin (Jurnal Pedagogy, 2025)
Gender representation in textbooks has a powerful impact on students’ perceptions and social identities. Unbalanced gender portrayal can influence how students view their roles and opportunities in society. This study aimed to investigate how gender is represented in educational material, English for Nusantara textbook for eighth-grade students. A mixed-method design was employed, combining content analysis and discourse analysis, to examine how often male and female characters are represented in the textbook. Brugeilles and Cromer's (2009) model was employed to inform analysis, focusing on the frequency of activities, roles, and characters' appearances. The findings revealed that male and female characters appear in nearly equal numbers however traditional gender roles are still dominated. Male characters are more frequently depicted in physical, competitive, and public roles, such as workers and rescuers, while female characters are more often shown in domestic, educational, and cultural contexts. These findings suggest that numerical balance does not necessarily indicate gender equality in representation. The study highlights the need for more diverse and equitable representation of both genders in educational materials. It also suggests that future research explores students' perceptions of gender and how teachers address gendered content in classroom settings to support more inclusive English language learning.